Standardizing outpatient total hip arthroplasty and empowering Canadian perioperative nursing practice - Head, Janelle (Operating Room Nurses Association of Canada Journal, 2026)
Decreased hospital length of stay in total hip arthroplasty procedures across Canadian hospitals and surgical facilities has led to the development of outpatient total hip arthroplasty (THA) programs. However, standardizing outpatient THA clinical guidelines with infused perioperative nursing input has not been comprehensively studied in Canadian hospitals and surgical centres. Therefore, this paper explores the current evidence, clinical standards, pathways, and organizational practices related to patient selection criteria, home environment support aspects, and healthcare team dynamics for existing outpatient THA in Canadian surgical facilities, as well as the level of perioperative nursing influence within these programs to date. Analyzing the existing literature on outpatient THA and related pathways in Canadian hospitals and surgical suites identifies key findings and areas for further development and standardization, as well as those challenges and barriers associated with implementation across Canadian healthcare systems.